Sistem Informasi Penjualan dan Pemesanan Online Berbasis Web pada Apotek Dua Farma - Nurrizki, Kiki Alfaini; Sumantri, Raden Bagus Bambang; Sandi A , Arif Setia (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2024)
Indonesian society increasingly relies on information technology in various aspects of life, including business and healthcare services. Pharmacies, as vital entities in healthcare, require information systems to manage data effectively. However, the Indonesian Ministry of Health states that more than 80% of healthcare facilities in Indonesia have not yet adopted digital technology, including Apotek Dua Farma, which manages 700 types of medicines and 100 manual transactions daily. This research aims to develop an online-sales and ordering information system based on a website using the Laravel framework at Apotek Dua Farma to address the difficulties in recording products and sales processes. The method used is Rapid Application Development (RAD), a fast and iterative linear sequential software development model. The research results indicate that the web-based information system developed has four types of users: admin, owner, pharmacist, and customer. This system successfully implements features such as product management, cashier system, online order processing, transaction tracking, reporting, and successfully applies the QRIS payment method. Blackbox testing shows that all features function well and meet the operational needs of Apotek Dua Farma, thereby improving the efficiency and accuracy of product recording and sales.